On dialogue - Bohm, David; Nichol, Lee (Routledge, 1996)
Never before has there been a greater need for deeper listening and more open communication to cope with the complex problems facing our organizations, businesses and societies. Renowned scientist David Bohm believed there was a better way for humanity to discover meaning and to achieve harmony. He identified creative dialogue, a sharing of assumptions and understanding, as a means by which the individual, and society as a whole, can learn more about themselves and others, and achieve a renewed sense of purpose.
Keywords: Dialogue analysis; Linguistics